Pemanfaatan Minyak Jelantah Jadi Sabun Padat - Lubis, Jeliana; Mulyati, Meylinda (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2019)
Pak Umar's Warung is a warung which produces used cooking oil up to 2.4 liters per day or 72 liters / month. Used cooking oil is sold to middlemen with a price per liter of Rp. 6,000 or Rp. 432,000.00 / month. Used cooking oil is used again for the frying process and this is dangerous. In this study, used cooking oil wasused to make solid soap for washing dishes and cloth. Before being made as a soap, used cooking oil must be cleaned from the dirt and purified. The process of deposition of used cooking oil uses rice flour absorbent. In the manufacturingof soap for washing, this required an investment of Rp 502,000. The production cost is Rp 1,129,152 for used cooking oil 57.6 liters obtained by HPP Rp 2,864.06, BEF Rp. 450,070.32 or 91 units and PP 0.28 days or 1 day and Profit of Rp1,740,858 / month. This means that used cooking oil is more profitable if it is turned into soap financially.